2011
DOI: 10.1016/j.avb.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Dating violence and substance use in college students: A review of the literature

Abstract: Dating violence is a serious and prevalent problem among college-aged dating couples. Although substance use has been shown to be associated with dating violence among college students in empirical studies, the use of substances as they relate to dating violence has yet to be systematically reviewed. The purpose of the present manuscript is to review research on dating violence (perpetration and victimization) and substance use (alcohol and drugs). First, theoretical explanations for the association between su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
175
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(193 citation statements)
references
References 80 publications
10
175
2
3
Order By: Relevance
“…In terms of risk factors, this study found in multivariate logistic regression analyses, in agreement with a number of studies 14,[16][17][18][24][25][26][27][28][29][30][31] , that having experienced childhood physical and sexual abuse, tobacco use, alcohol use in the context of sex, PTSD symptoms and depression symptoms were associated with IPV. In addition, sexual risk behaviour (having had two or more sexual partners in the past year) and having a history of an STI in bivariate analysis was found to be associated with IPV.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In terms of risk factors, this study found in multivariate logistic regression analyses, in agreement with a number of studies 14,[16][17][18][24][25][26][27][28][29][30][31] , that having experienced childhood physical and sexual abuse, tobacco use, alcohol use in the context of sex, PTSD symptoms and depression symptoms were associated with IPV. In addition, sexual risk behaviour (having had two or more sexual partners in the past year) and having a history of an STI in bivariate analysis was found to be associated with IPV.…”
Section: Discussionsupporting
confidence: 90%
“…Sociodemographic factors for IPV among university students may include, female gender (although some report similar proportions of IPV between females and males) 16,20,24,25 earlier year of study 18 being single 17,19 and residing in a campus residence 19 . Individual risk factors for IPV may include childhood physical or sexual abuse or other prior victimization as well as history of interparental violence 17,18,25,26 substance use (alcohol and tobacco use) 17,[27][28][29] posttraumatic stress disorder (PTSD), depression, and suicidal behaviour 14,16,24,30,31 and sexual risk behaviour, including sexually transmitted infections (STI) and HIV [32][33][34] . Protective factors may include lack of peer and parental social support 22 lack of life satisfaction 20,24 high religiosity 35 low perceived control 36 lower Gross national income but not family income 37 .…”
Section: African Journal Of Reproductive Health March 2016; 20 (1): 30mentioning
confidence: 99%
“…Although alcohol use is included as a situational factor thought to be associated with increased dating violence perpetration, the model does not specifi cally address how alcohol may infl uence this behavior. The proximal effects model provides one conceptual model to explain the link between alcohol use and dating violence and posits that acute alcohol consumption contributes directly to the perpetration of dating violence (Chermack & Taylor, 1995;Leonard & Quigley, 1999;Shorey et al, 2011). Specifi cally, alcohol consumption is thought to impair higher order cognitive processes that may otherwise serve to inhibit aggressive behavior (Giancola, 2000).…”
Section: Alcohol and Dating Violencementioning
confidence: 99%
“…Several other competing theories have been posited to explain the association between alcohol use and aggression, including the indirect effects and the spurious models (Leonard & Quigley, 1999;Shorey et al, 2011). In the indirect effects model, rather than a direct association between alcohol and aggression, alcohol consumption is thought to infl uence other variables (e.g., relationship satisfaction; Kelly & Halford, 2006), and these other variables in turn contribute to partner aggression (e.g., O'Leary et al, 1994).…”
Section: Alcohol and Dating Violencementioning
confidence: 99%
See 1 more Smart Citation